Proposta de um banco de questões de matemática contextualizado para a educação do campo em linha ao novo ensino médio do Paraná - Gehlen, Jardel Jose (2024)
The dissertation consists of proposing a question bank for teaching mathematics in rural high schools in Paraná. Initially, the historical moment experienced by rural education was contextualized. Subsequently, the guiding documents for the implementation of the New High School, at the national and state levels, were investigated in order to reveal the gap existing in the materials available for rural education in Paraná, and that the material proposed here attempts to fill. Later, based on official documents and the literature, the choice of contextualization as the principle that guided the development of the exercises present in the educational product was supported, and the process of creating it was discussed. Finally, the question bank is presented composed of 192 new exercises developed from the field context.